Hubungan antara Self-Talk dengan Motivasi Belajar Pendidikan Jasmani berdasarkan Jenis Kelamin - Lutfi Pasha Yanuari; Yusuf Hidayat; Teten Hidayat (Departemen Kesehatan Dan Rekreasi Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2026)
This study aims to analyze the relationship between self-talk and Physical Education learning motivation and examine the differences in learning motivation based on gender in students at Senior High School 7 Bandung. This study uses a quantitative approach with a correlational design. The research sample consisted of 235 students, which included 116 male students and 119 female students who were selected through purposive sampling techniques. The instruments used were the Self-Talk Scale (STS) to measure self-talk and the Perceived Locus of Causality Questionnaire (PLOCQ) to measure the motivation to learn Physical Education. Data analysis was carried out using the Pearson Correlation test and the Independent Sample T-test. The results showed a positive and significant relationship between self-talk and Physical Education learning motivation (r = 0.174; p = 0.008), with a relatively small contribution (R² = 0.03 or about 3%). In addition, there was a significant difference in learning motivation by gender (p = 0.008), where male students had a higher level of learning motivation than female students. These findings show that self-talk is one of the psychological factors that play a role in supporting the motivation to learn Physical Education.